Assessment of Sales Promotion Activities of Tingketbelle Silk Sleepwear Online Fashion Shop: A Basis for Improvement: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study evaluates the sales promotion activities of Tingketbelle Silk Sleepwear's onlinefashion shop. Based on the results of this study, this paper will assist the Tingketbelle SilkSleepwear online fashion shop in understanding the sales promotion activities. This studyutilized a descriptive research method to gather data from 50 respondents. A purposivesampling technique was employed to select respondents. The study presents data on thedemographic profile, sales promotion activities of Tingketbelle Silk Sleepwear, salespromotional activities affecting online sales, problems encountered by the respondents insales promotional activities of Tingketbelle Silk Sleepwear, and the improvement plan thatcan be proposed by the researchers. Statistical tools used were frequency, percentage, andweighted mean.Based on the data, the majority of respondents were 21-30 years old and had the highestfrequency and percentage of 62% in the respondents' profiles in terms of age. Females gotthe highest frequency and percentage of 82% in respondents' profiles in terms of gender.Customers were satisfied with the sales promotion activities of Tingketbelle Silk Sleepwearin terms of contests and bundles, and they were very satisfied in terms of raffles. The salespromotional activities affect online sales in terms of quality, affordability, and mode ofpayment, as respondents were very satisfied. With 35.71%, competition in giveawayscaused the highest percentage of problems encountered by the respondents of theTingketbelle Silk Sleepwear online shop.Based on the findings of the study, it is recommended to set a limited time for bidding to befair with the customers who were waiting and wanted to avail of the products. Reduce theminimum purchase amount to be part of the contest. More customers will buy more productsto join the contest. Lower the required amount to attract more customers to buy the products.Always update the customers for giveaway promotions.
Keywords: Business Administration